Upaya Meningkatkan Motivasi Belajar Siswa Kelas IV (EMPAT) SD N. 173434 Pollung Melalui Model Pembelajaran Problem Based Learning (PBL) - Tiarma Monika M Lumbanbatu (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
Motivation is something that is important for every person, perhaps even without motivation it will be difficult for us to achieve the expected goals. Therefore, movitavi is also very necessary for students in undergoing or pursuing education, both from the basic education level and also beyond.This motivation is especially important for students when taking part in teaching and learning activities, with this, students truly realize that the learning activities they undertake are really important and really only for their own benefit. So that students always make maximum efforts in participating in teaching and learning activities to develop their abilities.Without basic awareness and motivation from students regarding the importance of developing abilities through learning activities, they will lose direction and not know the benefits or goals and perhaps even learning activities will be a burden for them, not something interesting even if they are involved or take part in learning activities. on a daily basis.Students at the basic unit level (SD) may not yet be aware of or understand the motivation within themselves, as well as a fundamental and strong understanding of why they should take part in education. In addition, environmental factors (maintained) by the community regarding the world of education also influence their understanding, mindset and character in participating in learning activities at school.Based on the above, I try to build student motivation in teaching and learning activities through the problem based learning (PBL) learning model so that students experience interesting learning experiences, in an effort to increase their learning motivation. From the classroom action research activities carried out, it was concluded that this model can stimulate and increase students' motivation which actually shows the development of their learning achievements.